2013
DOI: 10.1038/nsmb.2594
|View full text |Cite
|
Sign up to set email alerts
|

Supersite of immune vulnerability on the glycosylated face of HIV-1 envelope glycoprotein gp120

Abstract: A substantial fraction of broadly neutralizing antibodies (bnAbs) in certain HIV-infected donors recognizes glycan-dependent epitopes on HIV-1 gp120. Here, we elucidate how bnAb PGT 135 recognizes its Asn332 glycan-dependent epitope from its crystal structure with gp120, CD4 and Fab 17b at 3.1 Å resolution. PGT 135 interacts with glycans at Asn332, Asn392 and Asn386, using long CDR loops H1 and H3 to penetrate the glycan shield to access the gp120 protein surface. Electron microscopy reveals PGT 135 can accomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
440
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 322 publications
(459 citation statements)
references
References 46 publications
18
440
1
Order By: Relevance
“…22, 71 As per the apex bnAbs, we identified this class by screening single B‐cell cultures, which led to the isolation of the PGT121/4, PGT128, and PGT135 families from three individual donors 22. Later epitope‐focused binding‐based screens yielded similar bnAbs 26, 27, 41.…”
Section: Specificity Of Hiv Bnabsmentioning
confidence: 99%
See 2 more Smart Citations
“…22, 71 As per the apex bnAbs, we identified this class by screening single B‐cell cultures, which led to the isolation of the PGT121/4, PGT128, and PGT135 families from three individual donors 22. Later epitope‐focused binding‐based screens yielded similar bnAbs 26, 27, 41.…”
Section: Specificity Of Hiv Bnabsmentioning
confidence: 99%
“…These bnAbs were shown to compete with 2G12, to lose binding activity upon EndoH deglycosylation22 and to bind to the N332 glycan and a gp120 protein epitope including the sequence GDIR 22, 27, 72. By comparing structural information generated for different families within this class, it was shown that the N332/GDIR epitope is accessed from a variety of angles by the different bnAbs, which use diverse binding modes, leading to its definition as a supersite of vulnerability 71. Furthermore, in contrast to some other bnAb classes, these high‐mannose patch bnAbs use a variety of V, D, and J germline genes and do not appear to share particular genetic traits required for binding this epitope 22, 71.…”
Section: Specificity Of Hiv Bnabsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the V3-glycan epitope centers on the glycan at N332, high-mannose glycans at other positions can variably be involved in the bnAb epitope (4649). Such diversity is reflected in crystal and electron microscopy structures by different angles of approaches of individual V3-glycan bnAbs (24, 28,45,46,4850) (Wilson and Ward, this volume). The V3-glycan bnAb class is of interest for vaccine development because it does not require extensive somatic hypermutation to develop neutralization breadth.…”
Section: Characteristics Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…MacLeod and colleagues isolated a V3-glycan bnAb lineage (the PCDN lineage ) with moderate neutralization breadth and potency (20). PCDN neutralization was sensitive to the H330A mutation (50, 59), depended more on the presence of glycans at positions N156, N301 and N332 and less on integrity of the GDIR motif; it also appeared to require interactions with hybrid glycans (20). …”
Section: Antibody-virus Co-evolutionmentioning
confidence: 99%